(untitled) - Gray, Shelley Shepard (Center Point Large Print, 2015)
"Emma, a widow with three daughters, and Jay, a widower with three sons, understand each other's struggles. When Jay's oldest son becomes engaged, Emma helps with the wedding preparations. Jay want to court Emma in earnest, but Emma's relatives are troubled by the prospect of her moving on"--
Keywords: Amish; Fiction; Large type books; Christian fiction; Love stories